2011
DOI: 10.4034/pboci.2011.112.17
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de Vida do Cuidador e Saúde Bucal do Indivíduo com Necessidade Especial

Abstract: Objetivo: Avaliar a qualidade de vida dos cuidadores primários de pacientes com necessidades especiais, e verificar se há repercussão da mesma na saúde bucal dos pacientes. Método: O estudo foi do tipo exploratório descritivo, com delineamento transversal e abordagem quantitativa. Foram convidados a participar todos os cuidadores de indivíduos normoreativos e com deficiência que frequentavam a clinica escola de duas universidades e de um centro de reabilitação no período de setembro de 2008 a junho de 2009, em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
0
4
0
2
Order By: Relevance
“…In the present study, most participants reported receiving benefits, which given individuals with disability a minimum capacity to lead a decent life 26,27 . However, the mothers of disabled children/adolescents belonging to lower social strata often leave their jobs to perform the daily care of their children 17,20,24 . Thus, the precarious living conditions seen among mothers/caregivers of the children/ adolescents, especially those with more severe CP, can exert a strong negative impact on the oral health care of these children/adolescents as well as the quality of life 28 of both the caregiver and child/adolescent, as perceived by the participants of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, most participants reported receiving benefits, which given individuals with disability a minimum capacity to lead a decent life 26,27 . However, the mothers of disabled children/adolescents belonging to lower social strata often leave their jobs to perform the daily care of their children 17,20,24 . Thus, the precarious living conditions seen among mothers/caregivers of the children/ adolescents, especially those with more severe CP, can exert a strong negative impact on the oral health care of these children/adolescents as well as the quality of life 28 of both the caregiver and child/adolescent, as perceived by the participants of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the growing production of studies addressing the need for oral health care on the part of patients with special needs 6,19 , such production remains insufficient 6,20,21 . There is a gap in knowledge regarding the perceptions of parents and caregivers regarding the oral health care that should be offered to children and adolescents with CP 5,6,20 on the different levels of health care that provide services for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Children 2 to 6 years old who were being assisted in Rehabilitation CRP at the time of the data collection took part in this study. Other studies also showed data of disabled children, with a low number of subjects in the sample …”
Section: Discussionmentioning
confidence: 99%
“…8 Figueiredo também demonstra que a maior dificuldade que os pais ou cuidadores têm, quando o aluno apresenta algum grau de limitação, é no uso do fio dental. 10 A respeito do questionamento se os cuidadores participaram de palestras sobre a saúde bucal, a maioria dos respondentes já participou desse tipo de atividade. Isso pode ter contribuído para que 87% das mães e/ou cuidadores terem avaliado a saúde bucal de seus filhos como regular e ótima.…”
Section: Methodsunclassified